Acute postpartum pulmonary edema in severe preeclampsia - Fernando Nathaniel; Freddy Dinata (Institute of Computer Science (IOCS), 2023)
Pulmonary edema is a feature of preeclampsia's severe end of the disease spectrum. It refers to excessive fluid accumulation in the pulmonary interstitial and alveolar spaces. We report a case 50-year-old G3P3 Sundanese woman who presented to the emergency department of Ciawi Regional General Hospital with progressive dyspnea after five days post-Cesarean section. On physical examination, her blood pressure was severely elevated. Her clinical manifestations, along with investigations, were consistent with pulmonary edema and preeclampsia was likely the cause. The patient started receiving antihypertensive, salt and fluid restriction, and diuretic. The patient improved clinically after five days of treatment. Acute pulmonary edema is a life-threatening event. Therefore, appropriate and adequate management and multidisciplinary interventions were necessary to manage this case.